Complexity-generating cascade reactions - Garrec, K (2018)
The development of complexity-generating reactions for the synthesis of molecules containing multiple quaternary centres has the potential to provide access to new 3D templates for the pharmaceutical and agrochemical industries as well as the efficient synthesis of biologically active natural products and fragments thereof. This thesis describes the development of radical cascade methodologies for the synthesis of complex spiro[4.4]nonanes, containing three adjacent quaternary centres, from linear precursors. Chapter 1 provides an introduction. The ambitious cascade cyclisation reaction which forms the basis of the work in this thesis is discussed along with its potential use in the generation of 3D templates and for natural product synthesis. An introduction to 3D templates and cascade reactions forms the majority of this chapter. Initial studies on a simplified cascade reaction using samarium diiodide forms the basis of Chapter 2. In Chapter 3, an efficient synthesis of cyclisation precursors is described along with oxidative radical cyclisation of these 1,3-dicarbonyl compounds using manganese(III) triacetate and copper(II) salts. The synthesis of unusual spirocyclic molecules is reported. In tandem with the radical cyclisations, anionic cyclisations were briefly investigated and are reported in Chapter 4. Chapter 5 details the development of a visible light-mediated radical cyclisation cascade. An atom-economical method has been developed to form complex spiro[4.4]nonanes, bearing three contiguous all-carbon quaternary centres, in an efficient manner from readily accessible starting materials. Full experimental details are reported for compounds reported in the thesis as well as NMR and other spectroscopic data for the spirocycles and other key compounds.